Chinese Ethnicity and Islamic Conversion: A Sociological Study of Behavioral Meanings of Islamic Conversion - Bambang Amir Al Hakim (SCHOOLAR: Social and Literature Study in Education, 2023)
Behavior Changing religions or changing religious beliefs or better known as religious conversions often occur in human social life. This is done in order to seek true happiness by establishing a new choice of belief (religion). Such phenomena often occur among the public, including the Chinese community, including at the Indonesian Hajj Muhammad Cheng Hoo Mosque complex in Surabaya. There it is often witnessed the phenomenon of people changing religions or religious beliefs or what is called the conversion from non-Muslims to Muslims, from non-Muslims to adherents of Islam. The phenomenon of religious conversion behavior is interesting to study and study from a behavioral perspective, the meaning and meaning of behavior to find out exactly what they are looking for in carrying out this religious conversion. This research is a qualitative approach. Data obtained from 17 respondents (informants). Data collection activities were carried out using the method of observation, interviews and documenting data deemed necessary. Data or information that has been collected in a qualitative research is then tested for its validity through the following techniques: (1). Triangulation method, (2). Triangulation of researchers, (3). Source triangulation, (4). Extend research time. The results of the study show that the motivation of the Chinese people to convert to Islam is based on the search for beliefs that are believed to be true that can calm their lives, to obtain true happiness in their true lives..